(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This essay seeks to outline some legal, political and social reflections on the Rule of Law demanded by the Republican Charter, in the light of the legal and jurisdictional matrix of Civil Law, which vivifies civil society, in the face of the judicial reflexes of constitutionality control. The reader is therefore invited to one of the most pulsating debates in the General Theory of Law, which is the prerogative of the people’s government to be protected by a jurisdictional sieve of constitutionality control and the answer to the following question: i) will the future Parliament be able to discipline stable unions differently from marriage for general purposes? These reflections will be answered from the perspective of international debates within the scope of the General Theory of Law, the criticisms of civilists on the subject and the paradigmatic decisions of the Federal Supreme Court (STF), including the decision in RE 878.694/MG. The answers will be presented in line with national socio-political demands, with a basis in international debates about the mission of the Judiciary and Parliament enshrined in Western Constitutions and in the 1988 Charter, 30 years in the making, under the guideline of recognizing the Law as a living, dynamic and evolving socio-political phenomenon - but one that is guided by classic guarantees of its political and axiological regime.